PHYSICS OF BLOODSTAIN PATTERN ANALYSIS - Afdhila, Zakia (Jurnal Biosains Pascasarjana, 2025)
Bloodstain patterns are one of the pieces of evidence that can be found at the scene. Bloodstain pattern analysis is carried out to help reconstruct the events or occurrences that caused the formation of the pattern. Analysis is based on a combination of physics, biology and mathematics. Factors that influence the formation of bloodstain patterns are: surface tension and viscosity, drag and gravity and their influence on speed, and the shape of bloodstains when falling. In addition, surface conditions can affect the pattern of blood produced. Determining the area of "‹"‹origin of the bloodstain is carried out based on the impact angle calculated from the length and width of the bloodstain pattern. The analysis carried out in the experiment shows that there is closure in the bloodstain pattern analysis due to the assumption of a linear trajectory and determining the angle of the bloodstain. Different impact speeds will produce different bloodstain patterns.